Female republicanism in Peru: The case of Zoila Aurora Cáceres (1877-1958) and Dora Mayer (1868-1959) - Sánchez Montenegro, Verónica Matilde (2023)
The work investigates a profile of citizenship that is situated within a conceptual spectrum that we call female republicanism. Which expressed demands for equality, justice and women's rights. It revolves around the female role as promoter of civicvalues in the citizens of the republic. The one with organic features - as a social body. Women will be the guarantors of the correct development in the public space of the republican agents, since they will be guided by civic virtues based on Christian values. We will show that Zoila Aurora Cáceres and Dora Mayer are relevant for having thought and expressed such importance of the female role in their writings. Our exhibition highlights the imprint that his reflection had on the formation of our common ideas about citizenship in Peru and Latin America.